Penatalaksanaan Benda Asing Esofagus - Ananda C. F. Maweikere; Steward K. Mengko; Olivia C. P. Pelealu (Universitas Sam Ratulangi, 2023)
Abstract: Esophageal foreign bodies are common cases in hospitals and if not treated immediately, may lead to serious complications. This study aimed to determine the various methods of esophageal foreign body management that can be performed. This was a literature review study. Data were searched from three databases, namely Clinical Key, PubMed and Google Scholar. The results obtained 11 literatures to be reviewed. In addition to esophagoscopy, there were several other management techniques, including medical management using proteolytic enzymes, glucagon, and nitroglycerin, and other operative management, namely procedures with a dual-channel endoscope, Foley catheter, and double fogarty balloon catheter according to the type and location of the foreign body obstruction. In conclusion, management of esophageal foreign bodies includes both medical and operative management according to the type and location of foreign body obstruction in the esophagus. However, esophagoscopy method is the gold standard for esophageal foreign body management. Keywords: esophageal foreign body; medical management; operative management; esophagoscopy Abstrak: Benda asing esofagus merupakan kasus yang sering ditemukan di rumah sakit yang jika tidak segera ditangani dapat menyebabkan komplikasi serius. Penelitian ini bertujuan untuk mengetahui berbagai metode penatalaksanaan benda asing esofagus yang dapat dilakukan. Jenis penelitian ialah suatu literature review. Pencarian data menggunakan tiga database yaitu Clinical Key, PubMed dan Google Scholar. Hasil penelitian mendapatkan 11 literatur untuk dikaji. Selain esofagoskopi yang sering digunakan, terdapat beberapa teknik penatalaksanaan lain yaitu tatalaksana medis dengan menggunakan enzim proteolitik, glukagon, dan nitrogliserin serta tatalaksana operatif lain yaitu prosedur dengan dual-channel endoscope, Foley catheter dan double Fogarty balloon catheter yang dapat dilakukan sesuai dengan jenis dan lokasi obstruksi dari benda asing. Simpulan penelitian ini ialah penatalaksanaan benda asing esofagus dapat dilakukan dengan tatalaksana medis dan operatif sesuai dengan jenis dan lokasi obstruksi benda asing di esofagus. Metode esofagoskopi merupakan baku emas untuk kasus benda asing esofagus. Kata kunci: benda asing esofagus; tatalaksana medis; tatalaksana operatif; esofagoskopi